KEMENARIKAN MEDIA PEMBELAJARAN BERBASIS TEACHMINT PADA MATA KULIAH MANAJEMEN PENDIDIKAN MAHASISWA PENDIDIKAN SEKOLAH DASAR - Perangin Angin, Laurensia Masri; Simanjuntak, Sorta; Sembiring, Masta Marselina; Pandiangan, Rinto (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
The aim of this research is to evaluate the feasibility, usefulness and efficacy of Teachmint-based learning resources in the Unimed PGSD Department of Educational Materials Management course using classroom management strategies. The ADDIE model—analysis, design, development, implementation, and evaluation—was used in this research and development project. In terms of product validity, the results of data revision and validation from media experts obtained a percentage of 84.35 in the very feasible category, while data validation findings from material experts obtained a percentage of 73.21% which was included in the feasible category. In terms of beauty, 91.60% of the results met the very attractive criteria. In terms of efficacy, students scored an average of 57.6 before the test and an average of 88.8 after the test. The results of the average value show that there are factors that influence the use of Teachmint-based learning resources.